Cytotoxic and Radiosensitizing Effects of Folic Acid-ConjugatedGold Nanoparticles and Doxorubicin on Colorectal Cancer Cells - Behnam Heshmatian; Zhaleh Behrouzkia; Mahshid Mohammadian; Zhino Moradi; Zeinab Mohammadi; Reza Zohdi Aghdam (Tabriz University of Medical Sciences, 2022)
Purpose: Radiotherapy is one of the most important therapeutic options used to treat cancers.Radiation effects can be improved using nanoparticles and chemotherapeutic drugs asradiosensitizing agents. The aim of the present study was to evaluate the effects of folic acidconjugatedgold nanoparticles (GNP-F) in combination with doxorubicin (DOX) and x-Rayirradiation in colorectal cancer (CRC) cell line (HT-29).Methods: The cell viability assay (WST-1) was performed to study the cytotoxic effects ofdifferent concentrations of DOX and GNP-F after 24 and 48 hours treatments. Then, the effectsof the GNP-F, X-Ray irradiation, and DOX drug in single and combined treatments wereexamined after 24 and 48 hours treatment with effective doses. Likewise, the caspase 3 geneexpression ratio and the caspase 3 activity were assessed after 48 h treatment. Moreover, themalondialdehyde (MDA) level was determined in treated and untreated cells.Results: When GNP-F (at a concentration of 70 μM) was combined with X-ray irradiation (2Gy) and DOX drug, induced more cytotoxic effects compared to the control group. The resultsof cell viability assay showed that GNP-F + X-Ray in combination with a low concentrationof DOX (0.25 × IC50) enhanced the cytotoxic effects of cells compared to related singletreatments. Caspase 3 gene expression ratio and caspase 3 activity increased in double andtriple combination treatments in comparison with the single groups. Moreover, the MDA levelincreased in triple combination compared to the single treatments.Conclusion: Our findings confirmed the potential anti-cancer effects of the GNP-F and DOX incombination with X-Ray irradiation in CRC cells.